Generation of biohybrid implants using a multipotent human periodontal ligament cell line and bioactive core materials. Issue 9 (19th February 2021) - Ono, Taiga; Tomokiyo, Atsushi; Ipposhi, Keita; Yamashita, Kozue; Alhasan, M Anas; Miyazaki, Yudai; Kunitomi, Yoshihiro; Tsuchiya, Akira; Ishikawa, Kunio; Maeda, Hidefumi
Abstract: We aimed to generate periodontal ligament (PDL) tissue‐like structures from a multipotent human PDL cell line using three‐dimensional (3D) bioprinting technology and to incorporate these structures with bioactive core materials to develop a new biohybrid implant system. After 3D bioprinting, single‐cell spheroids were able to form 3D tubular structures (3DTBs). We established three types of complexes using 3DTBs and different core materials: 3DTB‐titanium core (TIC), 3DTB‐hydroxyapatite core (HAC), and 3DTB without a core material (WOC). The expressions of PDL‐, angiogenesis‐, cementum‐, and bone‐related genes were significantly increased in the three complexes compared with monolayer‐cultured cells. Abundant collagen fibers and cells positive for the above markers were confirmed in the three complexes. However, more positive cells were detected in HAC than in WOC or TIC. The present results suggest that 3D‐bioprinted structures and hydroxyapatite core materials can function similarly to the PDL and may be useful for the development of a new biohybrid implant system. Abstract : In this manuscript, we constructed biohybrid implants from three‐dimensional (3D) printed‐structures produced by a multipotent human periodontal ligament (PDL) cell line and core material made of hydroxy‐apatite. Besides, we compared their viability, phenotypes, and functionality. Based on these results, we expect that these 3D‐structures might promote PDL's regeneration and become a part of a brand‐new biohybrid implant system.